The concept of meaning in contemporary sculpture in the Kurdistan Region (Al-Academy, 2025)
The concept of meaning is considered one of the most important topics present in all arts that has occupied the minds of critics. As we see, contemporary art, especially sculpture, has many readings. In this research, various works of contemporary sculpture in the Kurdistan Region are presented and researched in terms of (the concept of meaning) different artistic aspects of sculpture from identifying with the problem of meaning and objective content. Considering this, we see that the research process began with the research problem. This stems from the important and controversial question that accompanies the question (Is reading the concept of meaning and the contents of sculpture in the Kurdistan Region an open and multiple interpretation in terms of meaning) and is there polarization or is the work a closed and final interpretation and a single polarization to interpret the meaning?) Then the research turns to (the importance of the research and its objectives) then (the limits of the research and identifying the most important of them). Then the research includes three sections in the theoretical section, the first section entitled (The concept of meaning in philosophical and aesthetic thought) in terms of dialogue with the most important concepts and individual topics reflected in the artist himself, interpreting these concepts to the independent philosophical direction in which the concept of sculpture raises the problem of the concept of meaning. The second axis (the concept of meaning in terms of critical aesthetic ideas) reading the critical thought of a number of sculpture works according to the critical level of meaning that you understand, the third axis (the concept of meaning in terms of the objective and personal in contemporary sculpture in the Kurdistan Region) discusses understanding the concept of meaning in contemporary sculpture, and emphasizes the personal and objective thinking that its sculpture understands, and finally the methodology followed in analyzing the samples is the descriptive analytical method, followed by the research community and the sample chosen intentionally in order to achieve the research objectives, which are (3) samples of Kurdistan artists between the years (2018 and 2023), then the analytical tools to analyze the sample, and finally collecting the information obtained by the researcher in order to obtain data and information by analyzing it in detail and accurately, then the researcher chose the artistic achievements of Kurdistan artists that carried several meanings. It came in line with the research in order to achieve the research goal, then according to the analytical descriptive and analytical approach, and then reached the following most important results: The artist and the presence of events in society through his own thinking, in terms of meaning and expression, the difference in meanings in the artist's work is not a difference and contradiction, but rather a diversity of meanings in understanding the artwork by the viewer, and here the thought of contemporary artists in the Kurdistan Region at the current stage, what came to light, the works that were embodied and created in terms of meaning are a product that expresses the suffering of the Kurdish people and the ideas and issues that exist in the thinking of contemporary artists in the Kurdistan Region and the artistic achievements shine in the dominance of the thinking of artists in the Kurdistan Region in terms of expression and meaning for artwork and the excess in form to invent and create a new form that differs from the normal realistic form and exaggeration in form enhances the artistic impact in different ways to attract the audience through the aesthetic experience of new ideas. And the conclusions reached by this research, then presented the recommendations, then a list of the sources used by the researcher in this research.